Bisleuconothine A, an eburnane-aspidosperma bisindole alkaloid from Leuconotis griffithii - Hirasawa, Y.; Shoji, T.; Arai, T.; Nugroho, A.E.; Deguchi, J.; Hosoya, T.; Uchiyama, N.; Goda, Y.; Awang, K.; Hadi, A.H.A.; Shiro, M.; Morita, H. (Elsevier, 2010)
A new bisindole alkaloid, bisleuconothine A(1) consisting of an eburnane-aspidosperma type skeleton, was isolated from the bark of Leuconotis griffithii. The structure including absolute stereochemistry was elucidated on the basis of 2D NMR data and X-ray analysis. Bisleuconothine A(1) showed cell growth inhibitory activity against various human cancer cell lines. (C) 2010 Elsevier Ltd. All rights reserved.